Assessment of Hypertension Using Clinical Electrocardiogram Features: A First-Ever Review - Bird, Kathleen; Chan, Gabriel; Lu, Huiqi; Greeff, Heloise; Allen, John; Abbott, Derek; Menon, Carlo; Lovell, Nigel H.; Howard, Newton; Chan, Wee-Shian; Fletcher, Richard Ribon; Alian, Aymen; et al. (Frontiers in Medicine, 2020)
Hypertension affects an estimated 1.4 billion people and is a major cause of morbidity and mortality worldwide. Early diagnosis and intervention can potentially decrease cardiovascular events later in life. However, blood pressure (BP) measurements take time and require training for health care professionals. The measurements are also inconvenient for patients to access, numerous daily variables affect BP values, and only a few BP readings can be collected per session. This leads to an unmet need for an accurate, 24-hour continuous, and portable BP measurement system. Electrocardiograms (ECGs) have been considered as an alternative way to measure BP and may meet this need. This review summarizes the literature published from January 1, 2010, to January 1, 2020, on the use of only ECG wave morphology to monitor BP or identify hypertension. From 35 articles analyzed (9 of those with no listed comorbidities and confounders), the P wave, QTc intervals and TpTe intervals may be promising for this purpose. Unfortunately, with the limited number of articles and the variety of participant populations, we are unable to make conclusions about the effectiveness of ECG-only BP monitoring. We provide 12 recommendations for future ECG-only BP monitoring studies and highlight the limited findings in pregnant and pediatric populations. With the advent of convenient and portable ECG measurements in smart devices such as watches, understanding how to apply ECG-only findings to identify hypertension early is crucial to improving health outcomes worldwide.